2021
DOI: 10.1038/s41588-021-00897-w
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous disruption of PRC2 and enhancer function underlies histone H3.3-K27M oncogenic activity in human hindbrain neural stem cells

Abstract: Driver histone H3-K27M mutations are frequent in pediatric midline brain tumors. However, the precise mechanisms by which H3-K27M causes tumor initiation remain unclear. Here, we use human hindbrain neural stem cells to model the consequences of H3.3-K27M on the epigenomic landscape in a relevant developmental context.Genome-wide mapping of epitope-tagged histone H3.3 reveals that both wildtype and K27M-mutant incorporate abundantly at pre-existing active enhancers and promoters, and to a lesser extent at PRC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 67 publications
(105 reference statements)
7
43
1
Order By: Relevance
“…H3K27M mutation globally reduces H3K27 trimethylation (H3K27me3), leading to elevated expression of gliomagenesis genes [ 7 , 34 , 35 ]. Thus, research focused on reversing the H3K27 mutation effects through targeted upstream target inhibition or epigenetic therapy remains a viable treatment option [ 36 , 37 , 38 ].…”
Section: Pathogenesis: Stem Cell and Mutationmentioning
confidence: 99%
See 3 more Smart Citations
“…H3K27M mutation globally reduces H3K27 trimethylation (H3K27me3), leading to elevated expression of gliomagenesis genes [ 7 , 34 , 35 ]. Thus, research focused on reversing the H3K27 mutation effects through targeted upstream target inhibition or epigenetic therapy remains a viable treatment option [ 36 , 37 , 38 ].…”
Section: Pathogenesis: Stem Cell and Mutationmentioning
confidence: 99%
“…Somatic ACVR1 mutations are nearly exclusively limited to H3K27M-mutant diffuse midline glioma, occurring on only 0.3% of all other tumor types. These mutations induce hyperactive bone morphogenic protein (BMP) signaling, which arrests oligodendrocyte differentiation and increases tumorigenicity [ 36 , 37 ]. Specifically, Hoeman et al found that mouse tumor models with ACVR1 R206H plus H3.1K27M mutation had significantly shorter survival than tumor models with H3.1K27M mutations and no ACVR1 mutation [ 39 ].…”
Section: Pathogenesis: Stem Cell and Mutationmentioning
confidence: 99%
See 2 more Smart Citations
“…While global H3K27me2/3 levels were found to be decreased in DIPG expressing H3K27M, individual genes exhibit dramatically increased levels of the repressive H3K27me3 mark (Chan et al., 2013; Mohammad et al., 2017). This aberrant epigenetic profile might be explained by a confinement of PRC2 at its initial binding sites mediated by strong interaction of the mutant histone with EZH2, in turn leading to impaired spreading of the H3K27me3 mark (Brien et al., 2021; Chan et al., 2013; Voigt & Reinberg, 2013).…”
Section: Polycomb Regulation In Cancers Of the Cnsmentioning
confidence: 99%